Host range of some isolates of Magnaporthe grisea and their grouping into forma-specialis - R.A. SINGH, ARUN KUMAR and (Indian Phytopathology, 2002)
Magnaporthe grisea (Hebert) Barr. anamorph-Pyricularia grisea Sacc. is parasitic on a number of cereals and grasses belonging to the family Graminae. Cross inoculation tests by the isolates on different hosts have shown contradictory results as some workers have reported pathogenicity on a specific host, while others have failed in confirming the results. The present study was undertaken to ascertain these contradictory results by selecting seven isolates from 7 hosts from U.P., India more precisely.